2012
DOI: 10.1128/aac.00922-12
|View full text |Cite
|
Sign up to set email alerts
|

Telavancin in Therapy of Experimental Aortic Valve Endocarditis in Rabbits Due to Daptomycin-Nonsusceptible Methicillin-Resistant Staphylococcus aureus

Abstract: A number of cases of both methicillin-susceptible Staphylococcus aureus (MSSA) and methicillin-resistant S. aureus (MRSA) strains that have developed daptomycin resistance (DAP-R) have been reported. Telavancin (TLV) is a lipoglycopeptide agent with a dual mechanism of activity (cell wall synthesis inhibition plus depolarization of the bacterial cell membrane). Five recent daptomycin-susceptible (DAP-S)/DAP-R MRSA isogenic strain pairs were evaluated for in vitro TLV susceptibility. All five DAP-R strains (DAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…As observed in previous studies (6,39,47,48), S. aureus cell densities in cardiac vegetations were significantly higher than those in kidneys and spleens for each strain at 24 h postinfection (P Ͻ 0.01) ( Table 3). In the comparative virulence assessments, except for the ⌬lytSR complemented and ⌬lrgAB strains, which showed rather moderate decreases in cell densities in kidneys (Ͻ1 log 10 -fold; P Ͻ 0.05), no significant differences in bacterial densities were observed among the strain set in the three target tissues.…”
Section: Cap/hdp Susceptibility Profilessupporting
confidence: 68%
See 2 more Smart Citations
“…As observed in previous studies (6,39,47,48), S. aureus cell densities in cardiac vegetations were significantly higher than those in kidneys and spleens for each strain at 24 h postinfection (P Ͻ 0.01) ( Table 3). In the comparative virulence assessments, except for the ⌬lytSR complemented and ⌬lrgAB strains, which showed rather moderate decreases in cell densities in kidneys (Ͻ1 log 10 -fold; P Ͻ 0.05), no significant differences in bacterial densities were observed among the strain set in the three target tissues.…”
Section: Cap/hdp Susceptibility Profilessupporting
confidence: 68%
“…Fourth, our in vitro data above led us to evaluate the role of the LytSR TCRS in endovascular infections, using the IE model (6,41,43). In the current study, both the ⌬lytS and ⌬lrgAB strains were found to be equivalent to the parental strain in their capabilities to induce experimental IE, proliferate within the vegetative lesion, and then disseminate hematogenously to distant target organs.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…In brief, its efficacy and superiority compared with vancomycin or daptomycin has been documented in murine models of bacteremia or pneumonia by MRSA [105,106], in murine subcutaneous infection models, in rabbit endocarditis caused by MRSA, VISA, or daptomycin non-susceptible staphylococci [107][108][109], as well as in rabbit meningitis caused by penicillin-resistant pneumococcus [110,111]. It was equivalent to vancomycin or linezolid in a model of rabbit osteomyelitis caused by MRSA [112].…”
Section: Animal Pharmacodynamic Modelsmentioning
confidence: 99%
“…In this investigation, we evaluated (i) the MICs (11) and in vitro killing activities (12,13) of tedizolid, linezolid, and vancomycin against lux mutant methicillin-susceptible S. aureus (MSSA) (Xen29) and MRSA (Xen30) strains (4,14,15), (ii) the influence of these antibiotics on biofilm formation (16,17), and (iii) the real-time in vivo efficacy of tedizolid versus that of linezolid and vancomycin in a well-characterized model of murine subcutaneous catheter-related infection (18) caused by the MSSA or MRSA strain by using a novel bioluminescence in vivo imaging system (IVIS).…”
mentioning
confidence: 99%